Relationships among Work-Related Affective Feelings in Employees, Determined through Partial Least Squares Structural Equation Modeling (PLS-SEM) - Awad Aljuaid; Ashraf Alhujailli; Erman Çakıt; Waldemar Karwowski; Magdalena Anna Jaworek; Tadeusz Marek; Atsuo Murata (Applied Sciences, 2022)
Feelings significantly affect organizations in a variety of circumstances and areas. Many major events that affect people and organizations cannot be discussed without an understanding of the essential roles of feelings. In addition, work-related feelings can substantially affect employees’ health, well-being, productivity, and performance. The purposes of this research were (1) to validate the work-related affective feelings (WORAF) questionnaire in Arabic respondents, (2) to examine the relationships among four WORAF: happiness, anxiety, anger, and dejection, and (3) to compare the model results with those in Turkish respondents participating in a previous study. A survey with the following four components was conducted: (1) work-related feelings of happiness, (2) work-related feelings of anxiety, (3) work-related feelings of anger, and (4) work-related feelings of dejection. A paper-based survey was completed by 332 workers from various companies in Saudi Arabia. The key components of the research model were developed with partial least squares structural equation modeling (PLS-SEM). According to the findings, workplace dejection and anger considerably affected workplace anxiety. Similarly, work-related dejection, anger, and anxiety significantly affected perceived happiness. A comparison indicated similar results between Arabic and Turkish respondents.